Closing the Gap of Unmet Needs in Inflammatory Pain Management: Case Series of Predimenol for Pain - Rizaldy Pinzon (MEDICINUS, 2021)
Chronic inflammatory pain is major medical problem worldwide. Nonsteroidal anti-inflammatory drugs (NSAIDs) and selective cyclooxygenase (COX)-2 inhibitors are commonly used medications to treat chronic pain. However, these agents have been associated with serious gastrointestinal, renal and cardiovascular adverse effects. This limitation indicates a clear unmet need in terms of safety of current treatment options for the management of chronic inflammatory pain. Those adverse effects may caused by overlapping roles of COX-1 and COX-2 in physiological and pathophysiological processes. Predimenol is a herbal medicine that can be used to treat pain. Recent findings showed that these phytochemicals may directly act upon several inflammatory processes and offer compelling evidence that predimenol could reduce pain and inflammation. We report two cases and short review of the use of predimenol for pain management. Our review showed that predimenol formulations could be a valuable alternative treatment to relieve symptoms of pain with good safety profile. Further researches through large, high quality RCTs to investigate the clinical benefit of predimenol for pain management are needed.